Cathepsin S Activity Controls Injury-Related Vascular Repair in Mice via the TLR2-Mediated p38MAPK and PI3K−Akt/p-HDAC6 Signaling Pathway. Issue 8 (August 2016) - Wu, Hongxian; Cheng, Xian Wu; Hu, Lina; Takeshita, Kyosuke; Hu, Chen; Du, Qiuna; Li, Xiang; Zhu, Enbo; Huang, Zhe; Yisireyili, Maimaiti; Zhao, Guangxian; Piao, Limei; et al.
Abstract : Objective—: Cathepsin S (CatS) participates in atherogenesis through several putative mechanisms. The ability of cathepsins to modify histone tail is likely to contribute to stem cell development. Histone deacetylase 6 (HDAC6) is required in modulating the proliferation and migration of various types of cancer cells. Here, we investigated the cross talk between CatS and HADC6 in injury-related vascular repair in mice. Approach and Results—: Ligation injury to the carotid artery in mice increased the CatS expression, and CatS-deficient mice showed reduced neointimal formation in injured arteries. CatS deficiency decreased the phosphorylation levels of p38 mitogen-activated protein kinase, Akt, and HDAC6 and toll-like receptor 2 expression in ligated arteries. The genetic or pharmacological inhibition of CatS also alleviated the increased phosphorylation of p38 mitogen-activated protein kinase, Akt, and HDAC6 induced by platelet-derived growth factor BB in cultured vascular smooth muscle cells (VSMCs), and p38 mitogen-activated protein kinase inhibition and Akt inhibition decreased the phospho-HDAC6 levels. Moreover, CatS inhibition caused decrease in the levels of the HDAC6 activity in VSMCs in response to platelet-derived growth factor BB. The HDAC6 inhibitor tubastatin A downregulated platelet-derived growth factor–induced VSMC proliferation and migration, whereas HDAC6 overexpression exerted the opposite effect. Tubastatin A also decreased the intimal VSMC proliferation and neointimal hyperplasia in response to injury. Toll-like receptor 2 silencing decreased the phosphorylation levels of p38 mitogen-activated protein kinase, Akt, and HDAC6 and VSMC migration and proliferation. Conclusions—: This is the first report detailing cross-interaction between toll-like receptor 2–mediated CatS and HDAC6 during injury-related vascular repair. These data suggest that CatS/HDAC6 could be a potential therapeutic target for the control of vascular diseases that are involved in neointimal lesion formation. Abstract : Supplemental Digital Content is available in the text.